Peran Guru Ppkn Dalam Mewujudkan Misi Pendidikan Pancasila Dan Kewarganegaraan Sebagai Pendidikan Demokrasi Di SMP Negeri 2 Sawan - Leonardus Ludir (Jurnal Locus Delicti, 2021)
This study aims to describe (1) the role of PPKn teachers in realizing the mission of Pancasila and citizenship education as democratic education at SMPN 2 Sawan (2) the function as a manifestation of the development of democracy at SMPN 2 Sawan, in the research reveals the extracurricular role at SMPN 2 Sawan in realizing and implement the PPKn vision and mission as subjects that are focused on democratic values that will be implemented at SMPN 2 Sawan, what is the role of PPKn teachers in the mission of democratic education at SMPN 2 Sawan and also identify what things are done by teachers in building values the value of democracy at SMPN 2 Sawan. In this study, found several results that can be said to be good with several forms of research in the form of observation, interviews, documentation and questionnaires. In accordance with the reference to Law of the Republic of Indonesia Number 20 of 2003 concerning the national education system which has been internalized and implemented is sufficient as mandated by Law of the Republic of Indonesia Number 20 of 2003 concerning 18 character values.